Pelatihan Penerapan Kurikulum 2013 Guru Sekolah Dasar Negeri Dengan Metode Pendampingan - Dihamri Dihamri; Haimah Haimah; Abditama Srifitriani (Lembaga Layanan Pendidikan Tinggi Wilayah IX Sulawesi, 2020)
The purpose of the training is to help elementary school teachers who have difficulty in applying the 2013 curriculum. The method used is training using the mentoring method. Assistance is carried out directly and indirectly. The teachers were accompanied directly face to face by the service team in completing assignments, indirectly the teachers were accompanied by the team via telephone, email, whatsapp and videocall. To measure the achievement of the training is a qualitative descriptive analysis. To evaluate all activities using qualitative and quantitative methods. Qualitative data collection techniques are: interviews and observations, data analysis from beginning to end. Quantitative data collection techniques are questionnaires and data analysts using a percentage formula. The results of the training are teachers increasing curriculum competency in 2013